Genotype clinical phenotype analysis of 35 cases of hereditary spherocytosis in children - Duowen, Huang; Xia, Guo; Ju, Gao (Frontiers in Pediatrics, 2025)
ObjectiveHereditary spherocytosis (HS) is a common red blood cell membrane disease. It is currently clear that mutations in genes such as ANK1, SPTB, SPTA1, SLC4A1, EPB4.2 can cause the loss of their corresponding encoded proteins. However, there is a lack of reports in China on the association analysis between HS genotypes and clinical phenotypes, aiming to reveal whether there are differences in the corresponding clinical phenotypes of the same disease when genotypes are different.Methods35 children with HS who underwent complete whole exome gene sequencing in the Department of Pediatric Hematology at West China Second Hospital of Sichuan University from February 2014 to February 2024. Grouping according to different mutated genes/mutation types, and statistical analysis of blood routine and liver function indicators between different groups; Mann Whitney test analysis was used for inter group data processing, and significant differences were considered when both sides were p < 0.05.ResultsCompared with the SPTB group, the ANK1 group had significantly lower RBC (p = 0.021) and HGB (p < 0.01), but the differences in other indicators were not statistically significant (p > 0.05).ConclusionsAfter excluding potential influencing factors such as splenectomy, the anemia symptoms in ANK1-HS patients were more severe than those in SPTB-HS patients. However, there was no statistically significant difference in indicators between HS patients with different types of gene mutations.